2008
DOI: 10.3382/ps.2008-00147
|View full text |Cite
|
Sign up to set email alerts
|

Direct Enhancement of the Phagocytic and Bactericidal Capability of Abdominal Macrophage of Chicks by β-1,3–1,6-Glucan

Abstract: Salmonella enterica serovar Enteritidis is the major zoonotic and intracellular pathogen. Different strategies have been developed to prevent the S. Enteritidis infection. The beta-1,3-1,6-glucan of Schizophyllum commune was used as an immunological booster to determine the minimal dietary level of beta-glucan that would restrict S. Enteritidis infection through the effects of beta-glucan on the activity of macrophages and direct physical protection of the intestine. One-day-old male Single Comb White Leghorn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 23 publications
3
30
2
3
Order By: Relevance
“…The β-glucans appear to have functioned by increasing phagocytosis, bactericidal killing and oxidative burst from the heterophils. This was confirmed by Chen et al (2008) who reported that supplementation with yeast β-glucan enhanced the chick's defense against SE by directly upregulating both the phagocytosis and bactericidal activity of abdominal macrophages. Dietary supplementation of β-1,3-1,6-glucan of the fungus Schizophyllum commune was also shown to increase the phagocytic and bactericidal capabilities of intestinal macrophages (Chen et al, 2008;Muthusamy et al, 2013).…”
Section: Glucansmentioning
confidence: 64%
See 1 more Smart Citation
“…The β-glucans appear to have functioned by increasing phagocytosis, bactericidal killing and oxidative burst from the heterophils. This was confirmed by Chen et al (2008) who reported that supplementation with yeast β-glucan enhanced the chick's defense against SE by directly upregulating both the phagocytosis and bactericidal activity of abdominal macrophages. Dietary supplementation of β-1,3-1,6-glucan of the fungus Schizophyllum commune was also shown to increase the phagocytic and bactericidal capabilities of intestinal macrophages (Chen et al, 2008;Muthusamy et al, 2013).…”
Section: Glucansmentioning
confidence: 64%
“…A β-glucan from mushrooms has been shown to promote splenocyte proliferation and interleukin-2 production in broilers (Chen et al, 2008). Purified β-glucan from the edible mushroom Pleuratusflorida was shown to provide broiler chicks with some protection from Newcastle disease (Paul et al, 2012).…”
Section: Glucansmentioning
confidence: 99%
“…Serovars S. Enteritidis OU7586, an invasive strain of S. Enteritidis OU7439 to chicks (Chen et al, 2008), S. Pullorum OU7115 and OU7116, S. Gallinarum OU7113 and OU7114 of serogroup D Salmonella, and Escherichia coli OU4092 were used. The use of all bacteria and the animal experiments were approved by the Biological Security Committee, the Animal Use Protocol (IACUC No.99022), and the Institutional Animal Care and Use Committee of National Chiayi University in accordance with the laws of Taiwan (ROC).…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…The molecular weights and amounts of branches of the glucans can mediate different immune response in cytokines productions such as IL-12, IFN-γ, TNF-α etc. (Du et al, 2006;Rice et al, 2005;Suzuki, Hashimoto, Ohno, Tanaka, & Yadomae, 1989), as well as enhancement of phagocytic activities and productions of reactive oxygen species (ROS) against bacterial infections by Staphylococcus aureus, Streptococcus pneumoniae, and Salmonella enterica serovars Enteritidis (S. Enteritidis; Hetland, Ohno, Aaberge, & Lovik, 2000;Zhang, Cheung, Ooi, & Zhanf, 2004;Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%